Percutaneous Biliary and Gallbladder Interventions: Where Should Interventional Radiology Be Headed? - Riaz, Ahsun; Husnain, Ali (Digestive Disease Interventions, 2025)
Interventional radiology (IR) has evolved significantly in the past three decades due to improvements in techniques and technologies. The role of IR in managing biliary and gallbladder disease is evolving. A factor that has influenced our ability to perform advanced procedures has been the progress in endoscopes and their availability to IR. In addition to urgent or emergent decompression for these tubular structures and hollow organs, IR can also perform definitive therapies such as stenting and lithotripsy. The main objective of our therapies should be to remove drains as quickly as possible to improve patients' quality of life. The evolution of IR's role in this space is ongoing and should focus beyond decompression on treating the disease and the patient.
Keywords: biliary interventions; future directions; endoscopy